Goal striving, idiosyncratic deals, and job behavior. (23rd May 2015) - Ng, Thomas W. H.; Lucianetti, Lorenzo
Summary: Two important gaps remain to be filled in the idiosyncratic deals (i‐deals) literature. First, it is unclear which employees are predisposed to seek and receive i‐deals. Second, it is unclear how employees' perceptions of whether their coworkers are receiving i‐deals affect their own i‐deal experiences. This study proposed a theoretical model suggesting that (a) three key motivational goals identified in human development research, that is, achievement, status, and communion striving, predispose employees to seek and receive i‐deals; (b) employees' perceptions of whether their coworkers are receiving i‐deals moderate these relationships; and (c) employees' i‐deals are related to their job behavior. Data collected from more than 400 working adults in Italy showed that employees' motivational goals (particularly achievement and status striving) were positively related to the levels of i‐deals they received, and that these i‐deals were in turn positively related to supervisors' assessments of their in‐role job performance, voice behavior, and interpersonal citizenship behavior. High perceptions of the extent to which coworkers received i‐deals further strengthened the relationship between status striving and employees' perceptions of their own i‐deals, highlighting a trait‐situation interactionist perspective on employees' i‐deal experiences. Copyright © 2015 John Wiley & Sons, Ltd.